The impact of high food prices on food security - alyakobi , Salsabil A.; Hakam , Abdul Razzaq A.; Ben hamed, Usama M. (Journal of Pure & Applied Sciences, 2021)
The FAO report of 2018 noted that the ongoing conflict in Libya has led to deterioration in the situation food security situation. The reports have pointed out that 24% of Libyan migrants are food insecure and up to 62% are at risk of food insecurity. It also pointed out that most Libyan families are reducing the amount of food consumption and are now eating the same meals without taking much care about the quality of the food. The study has targeted a random sample from Tripoli, city to determine the impact of high food prices on food security by paper and an electronic questionnaire containing 28 questions distributed to 200 people, Where 49.5% females and 50.5% males, ages are from 20 to more than 40 years old, Where the data columns were used as a tool for statistical data, in addition to identifying the relationship between income and family size in the city of Tripoli and their spending on food goods and what are the implications of that, using the econometrics program (Gretl) in estimating Food expenditure function. The study pointed out that these individuals rely on starchy foods because of cheap prices; they avoided food with high nutritional value because of high prices or lack of money to purchase them. Rising prices due to deterioration of the security situation may lead to one of the diseases of malnutrition and this of course, is contrary to the definition of food security, which should care of reaching financially to adequate, safe and nutritious food to meet their nutritional needs for an active and healthy life. The study concluded that 66% of its members were affected by the quality and 63% were affected by quantity of the meal they consume because of its high price. Which means that the prices have a massive impact on quality, quantity and the size of the individuals consumed meal, thus it may threatens their food security